2017
DOI: 10.1504/ijpm.2017.080917
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent sourcing and supplier opportunism

Abstract: Abstract:The term 'concurrent sourcing' refers to the practice of a firm to simultaneously make and buy the same components. This paper presents an agency model for explaining how and when concurrent sourcing reduces the likelihood of external supplier opportunism. In the proposed model, the external supplier's expected costs of opportunism are determined as a product of four factors. These four factors are: buyer's likelihood of discovering supplier opportunism, buyer's internalised quantity as reaction to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Wagner (2006) and El Ouardighi and Shniderman (2019) observed such behavior in direct supplier development programs. Yan and Kull (2015), Mols (2017), and Villena, Choi, and Revilla (2019) reported a similar behavior in other aspects of buyer–supplier interorganizational relationships. To avoid such supplier opportunism in capacity expansion projects, the buyer has to decide on how to improve the supplier's performance while ensuring that the supplier will exert enough effort to improve its capacity.…”
Section: Introductionmentioning
confidence: 73%
“…Wagner (2006) and El Ouardighi and Shniderman (2019) observed such behavior in direct supplier development programs. Yan and Kull (2015), Mols (2017), and Villena, Choi, and Revilla (2019) reported a similar behavior in other aspects of buyer–supplier interorganizational relationships. To avoid such supplier opportunism in capacity expansion projects, the buyer has to decide on how to improve the supplier's performance while ensuring that the supplier will exert enough effort to improve its capacity.…”
Section: Introductionmentioning
confidence: 73%
“…Indeed, it has been found that concurrent sourcing decreases the negative effects of both technological and performance uncertainty (Mols et al 2012). In addition, it increases the internal agent's monitoring power and reduces the opportunism of the external supplier (Mols 2017). It mitigates agency costs, signals quality and gives bargaining power the internal agent or franchisor (Hefetz, Warner, and Vigoda-Gadot 2014).…”
Section: Mixed Deliverymentioning
confidence: 99%